Vibration control of semi-active suspension with MR damper by optimal preview control of MLD model. - Kaoru SATO; Kazuhiko HIRAMOTO (Nihon Kikai Gakkai ronbunshu, 2022)
Advances in image processing technology have made it possible to measure the surface shape of the road ahead while driving. We propose a new semi-active suspension control method considering the forward road surface shape. A vehicle model equipped with a semi-active suspension can be expressed as an MLD (Mixed Logical Dynamical) model. When the shape of the road ahead can be measured accurately, it can be considered that the information on the future disturbances is available before the vehicle undergoes. In this paper, we formulate the finite time optimization problem of an MLD model to consider future disturbances as an MIQP (Mixed Integer Quadratic Programming) problem in the same way as the conventional optimal control problem without future disturbance. The solution to an MIQP problem can be obtained by a commonly available solver software. The performance evaluation of the proposed method was carried out by a simulation, and the simulation was performed on the road surface shape generated based on ISO 8608. In the simulation study, the proposed method achieved better ride comfort, i.e., equivalent suspension stroke, compared to the traditional MLD predictive control and the Skyhook approximation methods.